Kavramlarla Oynamak: Ziya Gokalp Du?uncesinde Ulusotesi Kategoriler ve Beynelmileliyet Kavram? - Bas, Muhammed Fazil; Akyurt, Mehmet Ali (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2022)
The chronological changes in Ziya Gokalp's thought have been discussed from various perspectives in the literature such as in relation to global political developments, Turkish political history, or Gokalp's biographical periods. Although these studies have widely emphasized the distinction between culture and civilization, the conceptual projections of Gokalp's intellectual transformation have yet to be analyzed in terms of the transnational dimension, which is in fact an inseparable part of political ideologies. Gokalp reinterpreted concepts quite dynamically according to current needs and brought them together into binary or ternary groups. Even the conceptual duo of culture and civilization, where the first represents nationality and the second represents transnationality, did not appear in any one single form throughout Gokalp's intellectual life. This study focuses on four moments regarding Ziya Gokalp's thought: his article Eskinin Mukavemeti [The Resistance of the Old] published in 1911, the two versions of his series of writings entitled Turklesmek, Islamlasmak, Muasirlasmak [Turkification, Islamization, Westernization] as journal articles in 1912-1914 and as a book in 1918, and finally his Turkculugun Esaslari [The Principles of Turkism] published in 1923. In this way, we aim to examine the continuity and breaks between Gokalp's proposals regarding Turkey's position by focusing on transnational categories, with a special focus on the concept of internationality. Gokalp developed various concepts such as civilization, family, ummah, modernity, tehzip [refined culture], cosmopolitanism, and ultramontanism to describe Turkey's various transnational relations in the direction of Ottomanism, Turkishness, Islam, and the West. This study discusses these transnational concepts and aims to analyze the international dimension of the sociopolitical proposal Gokalp developed in response to the historical and structural problematics of the Turkish state and society.
Keywords: Turkish sociology; History of sociology; Ziya G?kalp; History of concepts; Transnationality; Internationality; Sociology